(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Medicinal herbs have been known for their use as an alternative medicine in the management and treatment of different categories of diseases. The present study was designed to assess the phytochemical constituents present in methanol and ethylacetate leaves extract of Talium trangulare and its antioxidant potentials against free radicals comparatively. The functional groups of the phytochemicals were carried out using FTIR techniques while the phytochemical component of the extract was determined by standard methods. The comparative studies of antioxidant abilities of methanol and ethylacetate leaves extracts of Talium trangulare were evaluated by various antioxidant assays, including 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydrogen peroxide, hydroxyl radicals, scavenging activities. These different antioxidant activities were compared with standard antioxidants compounds such as ascorbic acid and Gallic acid. The total phenolic content in ethylacetate extract is higher than what was obtained from methanol extract of Talium trangulare, however, methanol extract has higher tannins and flavonoids content. The methanol extract was found to have demonstrated high reduction capability and powerful free radical scavenging, especially against DPPH radical and hydrogen peroxide as compared with the ethylacetate leaves extract. The results that was obtained in the present study clearly established the antioxidant potency of both ethylacetate and methanol leaf extracts of Talium trangulare. The methanol extract shows better antioxidant activities and more flavonoids and tannin than the ethylacetate extract. In conclusion, the methanol leaf extract of Talium trangulare has comparatively better in vitro antioxidant potentials with corresponding phytochemical content than ethylacetate extract.